2000
DOI: 10.1177/107110070002100109
|View full text |Cite
|
Sign up to set email alerts
|

Chronic Recurrent Subluxation of the Peroneal Tendons in a Pediatric Patient. Surgical Recommendations

Abstract: Numerous surgical and non-operative approaches have been used to treat chronic recurrent subluxation of the peroneal tendons in adult athletes. There have been no published reports of surgical repair in children. In this report on a skeletally immature patient a modification of the Chrisman-Snook procedure (previously described for lateral ligament reconstruction) is described to correct recurrent subluxation of the peroneal tendons, child.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 16 publications
0
5
0
Order By: Relevance
“…There are a few studies available on the treatment of peroneal tendon dislocation in the paediatric population. All authors reported cases operated on by an open approach and a calcaneofibular transfer [2, 4]. Stenquist et al thus concluded that there was a high risk of post‐operative stiffness that could be a limitation of the above‐mentioned procedure in children [19].…”
Section: Discussionmentioning
confidence: 99%
“…There are a few studies available on the treatment of peroneal tendon dislocation in the paediatric population. All authors reported cases operated on by an open approach and a calcaneofibular transfer [2, 4]. Stenquist et al thus concluded that there was a high risk of post‐operative stiffness that could be a limitation of the above‐mentioned procedure in children [19].…”
Section: Discussionmentioning
confidence: 99%
“…Hollis et al reported that inversioneversion subtalar motion was not significantly changed after augmented reconstruction [22]. Many studies have shown successful results with augmented ankle reconstruction procedures [3,14,19,23,28,30,34,35,[37][38][39][40].…”
Section: Discussionmentioning
confidence: 99%
“…The surgery may be complicated by the presence of open fibular growth plates; care must be taken to not interrupt these growth plates in pediatric patients [6]. Peroneal subluxation in pediatric patients with open physes is uncommon with the first case of surgical correction of this condition in a pediatric patient with open physes being reported in 2000 [7].…”
Section: Case Description Presentation and Imagingmentioning
confidence: 99%